Answer:
The first four terms is: 390625, 625, 25, 5
Step-by-step explanation:
Given
[tex]f(n) = \sqrt{f(n-1)}[/tex]
To determine the first 4 terms.
We have
[tex]f(1) = 390625[/tex]
[tex]f(2) = \sqrt{f(2 - 1)}[/tex]
[tex]f(2) = \sqrt{f(1)}[/tex]
Substitute 390625 for f(1)
[tex]f(2) = \sqrt{390625}[/tex]
[tex]f(2) = 625[/tex]
For f(3), we have
[tex]f(3) = \sqrt{f(3-1)}[/tex]
[tex]f(3) = \sqrt{f(2)[/tex]
[tex]f(3) = \sqrt{625[/tex]
[tex]f(3) = 25[/tex]
For f(4), we have
[tex]f(4) = \sqrt{f(4-1)[/tex]
[tex]f(4) = \sqrt{f(3)[/tex]
[tex]f(4) = \sqrt{25[/tex]
[tex]f(4) = 5[/tex]
Hence, the first four terms is:
390625, 625, 25, 5